Effects of the combined vacuum pre-oxidation on the microcracks initiation and propagation of thermal barrier coatings deposited by means of plasma spraying. (February 2016) - Han, Y.J.; Zhu, Z.Y.; Ye, F.X.; Yang, G.; Chen, H.F.; Gao, Y.F.
Abstract: The chemical compositions and the residual stress of the thermally grown oxides (TGO) of thermal barrier coatings (TBCs) were characterized. Moreover, the relationship between the initiation and propagation of the microcracks in top coat and the evolution of TGO were systematically studied. The results indicate that the degradation mechanisms of TBCs prepared by atmospheric plasma spraying probably result from the weakened TGO area which is closely related to the change of the alumina phase transformation and the excessive presence of the spinel oxides as well as the propagation of the vertical surface cracks. Generally, the vertical surface cracks will propagate to the TGO area and subsequently meet with the horizontal cracks adjacent to the upper 50 μm area from the TGO. However, the propagation of the vertical surface cracks will be markedly suppressed when the strengthened TGO area occurs; while the initiation and propagation of the horizontal cracks above the TGO area can be significantly suppressed because the specific cracks aggregation can be found in the top coat. Furthermore, the textured (Al, Cr)2 O3 formed at the bottom layer of TGO can strengthen the oxidation and corrosion resistance of TGO. The maximum magnitude of the steady state release rate Gss can be delayed in the top coat, which can prolong the lifetime of TBCs. Highlights: Surface crack propagation will be suppressed when the TGO can be strengthened. Horizontal crack propagation is suppressed by toughened crack aggregation in topcoat. Textured (Al, Cr)2 O3 oxide at the bottom layer of the TGO can strengthen the TGO. It is favorable to TBCs if the Gss max within the ceramic coat is delayed.